곡류제품의 철 강화 시나리오 작성 및 평가 - 정해랑(Hae Rang Chung); 홍민지(Min Ji Hong); 오세영(Se Young Oh); Rafael Perez Escamilla (Korean journal of community nutrition, 2006)
Until now, South Korea does not have either fortification or enrichment program as intervention tools although the addition of micronutrients to foods is for the most part not regulated. The aim of this study was to determine which scenario would most effectively reduce the proportion of the population with low iron intake while not putting other population groups at risk of excessive intakes. In order to investigate potential dietary consequences of iron fortification we analyzed 2 day dietary record data (n=3,955) from the 2001 National Nutrition Surveys. The Proportion of the population consuming dietary iron less than the estimated average requirement (EAR) ranged from $12.4{\sim}87.5%$ depending upon gender and age group. Iron fortification at the level of 100% of Recommended Intake (RI) per 100g to breads and instant o. dried noodles was estimated to result in a 15% decrease of proportion of those with iron less than EAR, while putting 1.4 % of the population greater than the Upper Limit (UL). Iron fortification appeared to be the most effective for the $15{\sim}19$ year old age group, showing 39% reduction of iron intake insufficiency. The results suggest that carefully designed fortification or enrichment to staple foods may contribute to increase dietary iron intakes of Koreans, especially for the young population with a high prevalence of iron inadequacy. As the estimation in this study was based solely upon dietary intake data, iron intake from supplements should be considered in further studies.